Trichoderma harzianum in combination with carbendazim for integrated control of rice seedling blight - LI Min; YANG Qian; WANG Shu; DONG Hai; CHEN Yu-ling (浙江大学学报. 农业与生命科学版)
Control efficacies of Trichoderma harzianum TS1 in combination with carbendazim against rice seeding blight pathogens were investigated, and induced resistance of rice to the disease was conducted. Activities of POD, PAL, PPO and SOD in root extracts from T. harzianum TS1 plus carbendazim treated seed plots were higher than those from untreated control. Simultaneously, seed treated with this combination counted to 82.25% disease control in growth chamber, which was 26.87% and 9.90% higher than that resulted by treatment with T. harzianum TS1 and carbendazim alone. Field efficacies of combinations at three ratios exceeded the efficacies of the two agents used separately, indicating possible synergistic effects. Significant synergistic effect was observed in combination at ratio of 6 to 4, manifested by 44.46% and 11.66% higher efficacy than each agent. Seed treated with each combination resulted in a significant increase in shoot height, root length, total wet and dry weight compared with untreated control. T. harzianum TS1 had the ability to colonize the rhizosphere and rhizoplane of rice plants with mean population sizes above 104 and 103 cfu·g-1 fresh root, no significant treatment effects on colonization rate were found.